2016
DOI: 10.3892/ijmm.2016.2785
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 contributes to chondrocyte apoptosis in a rat model of osteoarthritis

Abstract: Aquaporins (AQPs) have been found to be associated with a number of diseases. However, the role of AQP-1 in the pathogenesis of osteoarthritis remains unclear. We previously found that AQP-1 expression was upregulated in osteoarthritic cartilage and strongly correlated with caspase-3 expression and activity. The aim of this study was to further investigate the association of AQP-1 expression with chondrocyte apoptosis in a rat model of osteoarthritis, using RNA interference to knock down AQP-1. For this purspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, AQP1 functions in the synovial tissue were not assessed in the present study and should be addressed in a future study. Second, a previous report showed that AQP1 expression positively correlated with caspase-3 expression and activity, suggesting that AQP1 promoted caspase-3 activation and thereby contributed to chondrocyte apoptosis and the development of OA ( 28 ). Thus, AQP1 roles in chondrocyte apoptosis should also be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, AQP1 functions in the synovial tissue were not assessed in the present study and should be addressed in a future study. Second, a previous report showed that AQP1 expression positively correlated with caspase-3 expression and activity, suggesting that AQP1 promoted caspase-3 activation and thereby contributed to chondrocyte apoptosis and the development of OA ( 28 ). Thus, AQP1 roles in chondrocyte apoptosis should also be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports have also described various AQP1 functions other than its role in water-dependent homeostasis ( 28 30 ). Meng et al ( 30 ) demonstrated that AQP1 enhances the migration of bone marrow mesenchymal stem cells by regulating the focal adhesion kinase and β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the author confirmed that the AQP1 inhibitor-bacopaside II inhibited the viability, migration and tube formation of endothelial cells, and enhanced apoptosis [35]. Furthermore, it was found that the knockdown of AQP1 expression in chondrocytes from osteoarthritic rats using siRNA reduced the activity and expression of caspase-3, which indicated that AQP1 conduced to chondrocyte apoptosis and osteoarthritis development [36]. Thereby, AQP1 could regulate angiogenesis and apoptosis of cell in multiple diseases.…”
Section: Discussionmentioning
confidence: 88%
“…There is a small amount of apoptosis in the normal cartilage tissue, which is usually confined to the surface of cartilage tissue (22). It is an essential physiological process to ensure the normal growth and development of cartilage, regulate function and maintain homeostasis (22). The excessive apoptosis in cartilage cells indicates pathological changes of cartilage tissue, which is considered to be the key factor leading to the onset of OA (20).…”
Section: Discussionmentioning
confidence: 99%